2023
DOI: 10.3390/cells12081181
|View full text |Cite
|
Sign up to set email alerts
|

Advanced 3D Models of Human Brain Tissue Using Neural Cell Lines: State-of-the-Art and Future Prospects

Abstract: Human-relevant three-dimensional (3D) models of cerebral tissue can be invaluable tools to boost our understanding of the cellular mechanisms underlying brain pathophysiology. Nowadays, the accessibility, isolation and harvesting of human neural cells represents a bottleneck for obtaining reproducible and accurate models and gaining insights in the fields of oncology, neurodegenerative diseases and toxicology. In this scenario, given their low cost, ease of culture and reproducibility, neural cell lines consti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 121 publications
0
10
0
Order By: Relevance
“…As previously mentioned, preclinical model recapitulation of non‐diseased tissue for non‐cancer contexts (e.g., rare diseases) is likely more informative than tumor recapitulation, due to multiple genomic abnormalities in malignancies. 44 , 45 When subsetting only GBM tumor‐derived cell lines and PDXs, we found PDX models and cell lines both correlate highest to GBM‐specific tumor tissue, followed by all other brain tumor tissue, and then non‐diseased brain tissue (Figure 2B ). While PDX model profiles correlated significantly higher to brain tissue regardless of disease context ( p < .0001, W = 410–455), the range of correlations for specific models overlapped between PDX and cell lines (rho .77–.89).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…As previously mentioned, preclinical model recapitulation of non‐diseased tissue for non‐cancer contexts (e.g., rare diseases) is likely more informative than tumor recapitulation, due to multiple genomic abnormalities in malignancies. 44 , 45 When subsetting only GBM tumor‐derived cell lines and PDXs, we found PDX models and cell lines both correlate highest to GBM‐specific tumor tissue, followed by all other brain tumor tissue, and then non‐diseased brain tissue (Figure 2B ). While PDX model profiles correlated significantly higher to brain tissue regardless of disease context ( p < .0001, W = 410–455), the range of correlations for specific models overlapped between PDX and cell lines (rho .77–.89).…”
Section: Discussionmentioning
confidence: 98%
“…However, we suggest that the comparison of cell lines to non‐diseased tissues is important for the selection of preclinical models that may better recapitulate non‐cancer disease contexts, considering genetic drift and other abnormalities of tumors. 44 , 45 We found that by using subsets of the most varying genes (i.e., 100, 1000, 5000, and 10 000), cell lines generally correlated less to their tissue of origin (both tumor and non‐diseased), and yet that the full gene sets correlated higher than any varying gene subset (median correlation rho = .82) (Figure 1A ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The human SK-N-AS neural cell line was used to determine the biocompatibility of the different scaffolds, since they are related to the nerve tissue and share surface proteins and other biomarkers with neural cells [64]. Moreover, they have a high in vitro proliferation capacity.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro models of neural tissues are emerging as a promising, more ethical and accessible way to study brain pathophysiology with respect to animal models. Indeed, their high controllability and observability have allowed the investigation of neurotoxicity, neuroprotection, drug screening and therapeutic assessment for different neuropathies [1][2][3]. The electrophysiological behaviour of cultured neuronal networks can be studied via patch-clamp, calcium imaging and microelectrode arrays (MEAs) [4].…”
Section: Introductionmentioning
confidence: 99%